A retrospective Study on Intestinal Injury from Blunt Abdominal Trauma - Muralidharan Kannaian; Bhaskara Rao Bezawada; Vinod K; Subash Chandra Bose (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Blunt abdominal trauma is the primary cause of morbidity and mortality. Suppose there are no indications of external trauma or changes in the patient's vital signs; blunt abdominal injuries might be complicated to identify at first. It is possible to lose a significant amount of blood without the abdomen appearing significantly different. A direct blow from blunt trauma can result in visceral damage and solid organ rupture, which can cause hemorrhage, peritonitis, and related pelvic injuries. The liver, small bowel, and spleen are the most frequently injured organs.